«Life Cycle Contract» in the field of Transport Infrastructure – the New Public-Private Partnership Mechanism - Veronica V. Turgeneva; Vladimir D. Sekerin (Модернизация, инновация, развитие)
Purpose: the purpose of this article is to analyze the Russian experience in using public-private partnership mechanism (further – PPP) for the supply and maintenance of rolling stock for Moscow public transport vehicle fleet under the «Life Сycle Сontract» (further – LLC). Overview of LLC, benefits, strengths and weakness identification are needed to achieve the objectives. Methods: methodological and theoretical background of the article based on feasibility study of LCC implementation projects as well as practical experience of LCC in CUE «Mosgortrans» and CUE «Moscow Metro». Information based on official data from Ministry of Economic development of the RF, Moscow Mayor official website, Moscow City Investment Agency. Results: research into LCC in PPP system, strengths and weaknesses identification will allow to minimize risks and to improve system. Conclusions and Relevance: this article proves that LCC model under the tready of of rolling stock procurement and maintenance contracts for Moscow public transport can provide a city with the new generation rolling stock, increase comfort and safety, obtain additional reliability assurance and timekeeping, remain high properties of rolling stock during exploitation period.